Impact of bandwidth on small-scale fade depth - Malik, W; Allen, B; Edwards, D; IEEE (2007)
This paper investigates the impact of channel bandwidth on fading in wireless channels using indoor measurements. The variation of channel energy over a local region is examined for narrowband, wideband and ultrawideband (UWB) channels, and the corresponding fade depth is evaluated. The relation between bandwidth and fade depth is then captured with a simple dual-slope model. The effect of antenna polarization and line-ofsight blockage is also investigated. We observe that the fade depth initially falls rapidly with bandwidth, reaching 4 dB at 1 GHz, but further reduction in fading with bandwidth is much slower. © 2007 IEEE.